BETON DENGAN SUBSTITUSI PELLET POLYPROPYLENE (PP) DAN PENGARUHNYA TERHADAP KUAT TARIK DAN KUAT LENTUR - Jalali, Nur Aisyah (FORUM BANGUNAN, 2013)
The increasing development of technology at this time, resulting in the need for facilities and infrastructure such as buildings, roads, bridges, and so is also increasing. This research aims to find the effect of plastic pellets as supplementary material or as a substitute for the coarse aggregate in weight-volume, tensile strength, and flexural strength of concrete due to the use of plastic pellets. Concrete mixture used cement, water, sand, and crushed stone, plastic pellets also replace some or all of the crushed stone. Pellet is a type of plastic waste polypropylene (PP) of bottled water containers are processed to resemble the shape of crushed stone. Concrete mix design used SNI 03-2834-2002 with a compressive strength of 20 MPa plan. Variations in the sample of concrete were levels of without pellets, pellet grade with 60%, 80%, and 100% of the volume of crushed stone. Specimens in the form of cylinders and beams were tested at 28 days. The test results of concrete with plastic pellets levels 60%, 80%, and 100% were weight-volume of concrete in a row at 1967 kg/m3, 1778 kg/m3, and 1676 kg/m3, tensile strength of concrete in a row at 1,52 MPa, 1,46 MPa, and 1,10 MPa, flexural strength of concrete in a row at 2,54 MPa, 2,61 MPa, and 2,19 MPa.